The Influence of Infrastructure Quality on Community Welfare in North Luwu Regency - Dicky Ade Anggriawan P; Sri Wahyuni Mustafa; Muhammad Ikbal (Manunggal Halim Jaya, 2026)
This study aims to analyze the condition of infrastructure quality, the level of community welfare, and examine the effect of infrastructure quality on community welfare in North Luwu Regency. This study uses a quantitative approach with a causal associative research type. The data used are primary data obtained through the distribution of questionnaires to 100 respondents from the North Luwu Regency community selected using a purposive sampling technique. Data analysis was carried out using validity tests, reliability tests, classical assumption tests, and simple linear regression analysis using the SPSS program. The results show that infrastructure quality has a positive and significant effect on community welfare. This is evidenced by the regression coefficient value of 0.634 and a significance value of 0.000 (<0.05), so the research hypothesis is accepted. The coefficient of determination (R²) value of 0.438 indicates that infrastructure quality is able to explain 43.8% of the variation in community welfare, while the rest is influenced by other factors outside the research model. These findings indicate that the better the quality, accessibility, and usefulness of public infrastructure, the higher the level of perceived community welfare. Therefore, local governments are expected to improve the quality and equity of infrastructure development as an effort to promote sustainable community welfare.